The effect of aerobic physical effort on the speed of reaction of the arms and the strength of the hands on some functional variables among handball players - الله, أ.م.د. هانا جلال فتح الله فتح; يونس, أ.م.د. محمد حازم يونس (Sulaimani Journal for Humanities, 2025)
The research aims to identify the effect of aerobic physical effort on the speed of reaction of the arms and the strength of the hands, and to identify the effect of aerobic physical effort on some functional variables among handball players. The research was conducted on a sample of Koya University handball team players for the academic year (2022-2023), which their number was. (14) players, aged (20-22) years, and chosen intentionally, which constitutes (85.71%) of the research population. The main research and field procedures done in the closed hall of the physical education faculty, and the results were collected and processed statistically using the system (Graphpad Prism8), and the researchers studied the following research variables (measuring the reaction speed of the arms, measuring the strength of the hands, measuring the pulse rate, and measuring the breathing rate). The study concluded that the physical aerobic effort of the Cooper test contributed to increasing the heart rate to (135R/min) An increase in the number of breathing times to (25) times/min, a decrease in the functional response to the reaction speed of the arms, as well as a decrease in the strength of the grip of the hands.
Keywords: aerobic physical effort; reaction speed; hand strength; functional variables; handball